Synthesis of deuterium-labeled analogs of the lipid hydroperoxide-derived bifunctional electrophile 4-oxo-2(E)-nonenal - Arora, Jasbir S. (2011)
Lipid hydroperoxides undergo homolytic decomposition into the bifunctional 4-hydroxy-2(E)-nonenal and 4-oxo-2(E)-nonenal (ONE). These bifunctional electrophiles are highly reactive and can readily modify intracellular molecules including glutathione (GSH), deoxyribonucleic acid (DNA) and proteins. Lipid hydroperoxide-derived bifunctional electrophiles are thought to contribute to the pathogenesis of a number of diseases. ONE is an α,β-unsaturated aldehyde that can react in multiple ways and with glutathione, proteins and DNA. Heavy isotope-labeled analogs of ONE are not readily available for conducting mechanistic studies or for use as internal standards in mass spectrometry (MS)-based assays. An efficient onestep cost-effective method has been developed for the preparation of C-9 deuterium-labeled ONE. In addition, a method for specific deuterium labeling of ONE at C-2, C-3 or both C-2 and C-3 has been developed. This latter method involved the selective reduction of an intermediate alkyne either by lithium aluminum hydride or lithium aluminum deuteride and quenching with water or deuterium oxide. The availability of these heavy isotope analogs will be useful as internal standards for quantitative studies employing MS and for conducting mechanistic studies of complex interactions between ONE and DNA bases as well as between ONE and proximal amino acid residues in peptides and proteins.